Narratives of history and the discursive construction of national identity in the Russian Republic of Karelia. - Tew-Street, Fraser Lewis Edward (The University of Edinburgh, 2015)
Although an element of our quotidian existence the manner in which national identity is produced is one of the most contested problems in the contemporary social sciences. One method of examining the production of national identity is to study the mechanism through which such identities are constructed in discourse. This study considers the use of historical narratives in the construction of differing formulations of national identity in the Russian Republic of Karelia. Using the tools of critical discourse analysis this study surveys the production of varying historical narratives in the Republic of Karelia and the fashion in which such narratives contribute to producing or deconstructing competing conceptions of national identity. This thesis uses an analysis of both mass media discourse and interview data to provide a thorough illustration of the production of narratives of Karelian history on public and private levels and their use in engendering or refuting opposing notions of Karelian identity. It shall examine how various historical events and tendencies are incorporated into contrasting narratives of the historical development of the Karelian people and their Russian, Finnish and Vepsian counterparts and how such narratives are used to justify or invalidate current political and social realities. The relationship between such narratives of history and other aspects of identity production is investigated alongside the difficulties of ethnic Karelians in producing and promoting such narratives to sustain an image of Karelian national identity. It shall also demonstrate the manner in which Karelian identity can be positioned through the use of such historical narratives as closer to or more distant from Russian or Finnish national identity. The narration of a history of Karelia as an area and the manner in which this can be deployed to incorporate or distance the region from conceptions of Russian or Finno-Ugric identity is also made evident.